“Where do you want to take your family firm?” : A theoretical and empirical exploratory study of family business goals - Rodrigo Basco (BRQ Business Research Quarterly, 2017)
Family business scholars assume that family business goals represent the nature of the firm's decision making and are driving forces (i.e., antecedents) of family firm behavior, performance, continuity, competitiveness, and sustainability. Without measuring family business goals, family business research—specifically, the family business theorizing process—is floating in the midst of assumptions used to justify observational descriptive data, such as differences between family and non-family firms and differences among various types of family firms. There remains a lack of clarity surrounding the theoretical definition of family business goals and an absence of methodological approaches to make the concept operative. In order to address this gap, this research applies an exploratory step-by-step methodology that combines both a theoretical and an empirical approach. First, following an inductive literature review, I theorize family business goals as a multidimensional concept combining two scales: economic versus non-economic orientation and family versus business orientation. Second, by using a unique Spanish database of family business, I use the partial least squares structural equation modeling method to confirm and extend the proposed theoretical multidimensional concept of family business goals."
Keywords: 650; Family firms; Family business goals; Socioemotional wealth; Family-oriented goals; Family business objectives